Study on the Processing Optimization for the Enrichment of Polyphenols and Flavonoids in Co-fermentation of Quinoa and Black Barley and Its Bioavailability - Huibin JIANG; Pan NIE; Wei LÜ; Lihua SONG (Shipin gongye ke-ji, 2024)
To effectively enrich the polyphenols and flavonoids in quinoa and black barley and improve their bioavailability, the optimized processing condition for the co-fermentation of quinoa and black barley with Lactobacillus kisonensis was established based on single factors and the response surface experiments using polyphenols and flavonoids as response indexes in present study. The effects of co-fermentation of quinoa and black barley on the release and bioavailability of polyphenols as well as its antioxidant activity were investigated via in vitro gastrointestinal digestion experiments. The results showed that the optimized fermentation condition was quinoa: black barley 1:2.4 (g/g), solid-liquid ratio 1:8.9 (g/mL), inoculation dosage 2.0%, fermentation time 36.7 h, and fermentation temperature 30 ℃. Under this optimized fermentation conditions, the polyphenols and flavonoids contents of co-fermentation grains were 364.90 and 264.36 mg/100 g, respectively, which were significantly higher than those of unfermented grains and single fermented quinoa or black barley (P<0.05). The results of in vitro gastrointestinal digestion experiments showed that the release amount of free and total phenols, total antioxidant activity and hydroxyl radical scavenging activity of the co-fermentation grains were significantly higher than those of unfermented grain as well as single cereal fermentation groups (P<0.05). Correlation analysis between antioxidant activity and polyphenols content exhibited obviously positive correlation with both free and total phenols content (P<0.05). In conclusion, co-fermented quinoa and black barley exhibited better enrichment of polyphenols and flavonoids, improvement of the bioavailability of polyphenols to some extent and enhancement of the antioxidant activity compared with those of single grain fermentation.